CpG-island methylation and epigenetic control of resistance to chemotherapy. (26th October 2004) - Teodoridis, J.M.; Strathdee, G.; Plumb, J.A.; Brown, R.
Abstract : Aberrant methylation of CpG islands (CpG-rich regions of DNA associated with the promoters of many genes) is associated with transcriptional inactivation of genes involved in tumour development. Genes involved in key DNA damage response pathways, such as cell-cycle control, apoptosis signalling and DNA repair can frequently become epigenetically silenced and methylated in tumours. This may lead to differences in intrinsic sensitivity of tumours to chemotherapy, depending on the specific function of the gene inactivated. Furthermore, chemotherapy itself may exert a selective pressure on epigenetically silenced drug sensitivity genes present in subpopulations of cells, leading to acquired chemoresistance. Clinical trials of epigenetic therapies are now in progress, and epigenetic profiling using DNA methylation will provide guidance on optimization of the use of these therapies with conventional chemotherapy, as well as helping to identify patient populations who may particularly benefit from such approaches.